(untitled) (REMUNOM, 2024)
This study aims to examine two pedagogical practices that have been incorporated into the teaching of mathematics in Brazil in recent years. We will investigate the evolution of these tools, highlighting how they have influenced the way mathematical knowledge is transmitted and acquired. The central emphasis will be on how digital resources have driven the rise and establishment of interactive and dynamic teaching approaches, providing students with increasingly engaging and customized learning experiences. This reflection is crucial to inspire the creation of more captivating educational approaches and more engaging teaching methods, aiming to enhance the learning and teaching of mathematics. By comprehending the intricacies of these changes, we will be more equipped to construct a future in which technology serves as a primary companion in readying students for the challenges ahead.